Comparing the Communicated and Actual Implementation of Corporate Social Responsibility Practice: Case Study of PT Bank Maybank Syariah Indonesia - , NEYSHIA AMALINA, Mahfud Sholihin, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study aims to analyze the disclosure as well as the practice of Corporate Social Responsibility conducted by PT Bank Maybank Syariah Indonesia. This study was done by comparing the Corporate Social Responsibility disclosure and its actual implementation conducted by PT Bank Maybank Syariah Indonesia. The analysis towards the Corporate Social Responsibility disclosure consists of the analysis towards the 2012 published report of PT Bank Maybank Syariah Indonesia such as the annual report, audited financial statements, and the report of Good Corporate Governance. The analysis towards the actual implementation was conducted by collecting the evidences which confirmed the actual practice or implementation of Corporate Social Responsibility in PT Bank Maybank Syariah Indonesia. The analysis for both of the Corporate Social Responsibility disclosure as well as its actual implementation was conducted based on the six themes of disclosure based on Islamic Social Reporting Index (ISR) and its conformity with the Sharia Enterprise Theory. The result of this study indicated that the disclosures of Corporate Social Responsibility activites reported by PT Bank Maybank Syariah Indonesia are supported by the evidences of the Corporate Social Responsibility actual implementation. However, the disclosures as well as the actual implementations of Corporate Social Responsibility in PT Bank Maybank Syariah Indonesia do not fulfill the criteria of Corporate Social Responsibility practice based on Islamic Social Reporting Index and Sharia Enterprise Theory.